Prinsip In Absensia Dalam Pemeriksaan Tindak Pidana Korupsi Ditinjau Dari Perspektif Due Process of Law - Atapary, Adolf Erens; Pasalbessy, John Dirk; Wadjo, Hadibah Zachra (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Courts in absentia in corruption have been pros and cons to date, there is an assumption that court in absentia is a violation of human rights because it is related to the human rights of the accused as a human being who has the right to defend himself in court, on the other hand The trial in absentia can be carried out as long as the whereabouts of the defendant are not known at all so that he cannot be presented at the trial trial due to running away (fugitive). Purposes of the Research: This writing aims to analyze and explain the existence of justice in absentia in the implementation of the criminal justice system in Indonesia in accordance with the principle of due process of law, to analyze and discuss the nature of the principle of due process of law in ensuring legal certainty and justice in the examination of criminal cases. Methods of the Research: Normative research method with the type of research is qualitative analysis. The problem approach used is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through methods of interpretation, harmonization, systematic and legal discovery. Results of the Research: The results of the study indicate that the judiciary in absentia can be implemented and does not violate human rights as long as it is implemented through the correct procedure and based on the provisions of the law. The trial in absentia aims to break the deadlock in the examination of defendants who are not present at the trial and efforts to save state finances, both those that have been corrupted and those that are still suspected of being related to corruption cases, both those that have been confiscated and those that have not been confiscated to be confiscated for the State through a court decision.